Long-Term Outcomes in Real Life of Lumacaftor–Ivacaftor Treatment in Adolescents With Cystic Fibrosis - Bui, Stéphanie; Masson, Alexandra; Enaud, Raphaël; Roditis, Léa; Dournes, Gaël; Galode, François; Collet, Cyrielle; Mas, Emmanuel; Languepin, Jeanne; Fayon, Michael; Beaufils, Fabien; Mittaine, Marie (Frontiers in Pediatrics, 2021)
BACKGROUND: The combination of the CFTR corrector Lumacaftor (LUM) and potentiator Ivacaftor (IVA) has been labelled in France since 2015 for F508del homozygote cystic fibrosis (CF) patients over 12 years. In this real-life study, we aimed (i) to compare the changes in lung function, clinical (e.g., body mass index and pulmonary exacerbations) and radiological parameters and in sweat chloride concentration before and after initiation of LUM/IVA treatment; (ii) to identify factors associated with response to treatment; (iii) to assess the tolerance to treatment. MATERIAL AND METHODS: In this tri-centre non-interventional observational cohort study, children (12-18 years old) were assessed prospectively during the two years of therapy, and retrospectively during the two years preceding treatment. Data collected and analysed for the study were exclusively extracted from the patients' medical electronic system. RESULTS: Forty adolescents aged 12.0 to 17.4 years at LUM/IVA initiation were included. The lung function decreased significantly during prior to treatment and increased after LUM/IVA initiation, becoming significant after 2 years of treatment. LUM/IVA significantly improved the BMI Z-score and sweat chloride concentration. By contrast, there was no significant change in exacerbation rates, antibiotic use or CT-scan scores. Age at LUM/IVA initiation was lower in good responders and associated with greater ppFEV1 change during the 2 years of treatment. LUM/IVA was well tolerated. CONCLUSION: In F508del homozygote adolescents, real-life long-term LUM/IVA improved the ppFEV1 trajectory, particularly in the youngest patients, nutritional status and sweat chloride concentration but not exacerbation rates or radiological scores. LUM/IVA was generally well tolerated and safe.